Reverse metagenomics reveals diverse quorum sensing systems in complex activated sludge community - Thow, Xin Qiang (2015)
Bacteria produce and respond to signal molecules to synchronize their population behaviours in a process known as Quorum Sensing (QS) signalling. The N-acyl homoserine lactone (AHL) QS system consisting of a pair of luxI/luxR gene homologs is one of the most well established QS systems. While AHL QS systems have been well studied mostly in cultivable bacterial populations, the role and diversity of AHL QS systems, where most bacteria are uncultivable, remain unknown. In this study, reverse metagenomics is used to screen for luxI/luxR gene homologs from a deeply sequenced metagenome obtained from an activated sludge community. A total of 12 AHL-producing LuxI homologs and 30 putative LuxR homologs were identified. The majority of the LuxI/LuxR homologs were found to be phylogenetically distinct from their counterparts discovered in bacterial isolates. Using mass spectrometry, these novel LuxI homologs were found to produce a wide variety of AHLs ranging from four to sixteen carbons on the acyl side chain. Our study demonstrates that QS signalling is abundant in nature and that the reverse metagenomics approach is effective in accessing the diversity of LuxI/LuxR QS systems among uncultivable bacteria in the environment.